Level of client satisfaction among family planning service users in semi-pastoralist areas of Southeast Ethiopia: a mixed-methods study - Eshetu, Hana; Tesfaye, Dawit Jember; Fantahun, Selam; Birhanu, Bezawit; Deffecho, Daniel Dere; Teshager, Shitalem Tadesse; Meka, Beka Teressa; Gufue, Zenawi Hagos (Frontiers in Global Women's Health, 2024)
Background Client satisfaction with family planning services is a crucial metric for gauging healthcare providers' performance. There is a dearth of local data that explores the factors that influence clients' satisfaction with family planning services in semi-pastoral areas using a mixed-methods approach. This study aimed to assess the level of client satisfaction and its associated factors among family planning service users in six public health centers in Southeast Ethiopia. Methods A multi-centered, concurrent, mixed-method survey using quantitative and qualitative methods was conducted in six public health centers in Southeast Ethiopia from March 15 to April 16, 2022. Four hundred nineteen systematically selected family planning method users and their respective six family planning service providers were approached using a purposive sampling technique. A multivariable binary logistic regression model was used to identify the independent factors associated with clients' satisfaction with family planning services. Results Four hundred fourteen study participants were finally approached, and client satisfaction with family planning services in those centers was 57.5% with a 95% CI of 52.71%–62.71%. Being in the age group of 25–34 years (AOR = 1.99; 95% CI 1.2, 3.29), married (AOR = 2.41; 95% CI 1.13, 5.15), waiting less than 30 min (AOR = 1.74; 95% CI 1.11, 2.72), and receiving the family planning method they want (AOR = 2.35; 95% CI 1.16, 4.76) were positively associated with client satisfaction. Updating the provider's skills and knowledge, keeping clients' method choices, and leaving free decisions also increased client satisfaction. Conclusions In this study, client satisfaction with family planning services remains low. Users' age, marital status, waiting time, and wish to receive the method they want were positively associated with client satisfaction.